(untitled) (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-58-66 The aim of the study, conducted on the material of French theological vocabulary, is to demonstrate the influence of Catholicism on various political and social processes in medieval France. The religious terms were selected from historical literature and subjected to the linguacultural analysis in the diachronic context. French religious terminology as a layer of theological vocabulary goes back to Greek and Latin. Many verbs acquire religious meaning precisely within the framework of the churchreligious context. Being verbal manifestation of concepts associated with the Christian faith, religious terminology reflects the special role of the Catholic Church as a socio-political institution in the formation of the French national state. The research helps to trace the inextricable connection between religion, history and language as a complex system of verbal expression of the cognitive and social activity of French people. The obtained results have theoretical significance for modern French linguistics as a multidisciplinary paradigm, as well as practical value for linguodidactics, foreign language teaching methods, and lexicography. In addition, the analysis of the role of the church in the formation of French national statehood, carried out on the basis of religious terminology, contributes to understanding the position of modern French right-wing and ultra-right political formations, which consists in preserving French identity and rejecting concepts of human existence alien to French culture. Key words: theological vocabulary, religious terminology, Frankish state, history of France, Catholic Church, French linguistics, Romance studies